Energy consumption model for density controlled divide-and-rule scheme for energy efficient routing in wireless sensor networks. (2016) - Latif, Kamran; Javaid, Nadeem; Saqib, Malik Najmus; Khan, Zahoor Ali; Alrajeh, Nabil
In wireless sensor networks (WSNs), sensor nodes (nodes) are equipped with limited energy source. Therefore, efficient energy utilisation of nodes has become a hot research area in WSNs. In this paper, we introduce a new routing technique for WSNs in which, we solve the problem of unbalanced energy utilisation, which causes energy and coverage holes in WSNs. Deployment area is divided into subareas; each subarea logically represents a static cluster. Dividing network field into subfields helps to control coverage hole problem whereas, static clustering helps to avoid energy hole problem. Mathematical formulation of the proposed work is provided to analyse and verify our technique. Simulation results show that our technique balances energy utilisation of the network.